Kepuasan Kerja Memediasi Hubungan Komitmen Organisasi terhadap Turnover Intention - Dewintasari, Dewintasari (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2024)
This study aims to determine the effect of organizational commitment on turnover intention through job satisfaction as a mediating variable at PT Bank Tabungan Negara (Persero) Tbk Medan Branch Office. Path analysis research design is used as an analytical tool to determine the direction of the variables studied and to justify how significant the influence of the independent and dependent variables is through the mediating variable. In this study using an associative method with a quantitative approach. The total population in this research is 172 employees and a sample of 120 employees at PT Bank Tabungan Negara (Persero) Tbk Medan Branch Office.The results of this study indicate that the variable organizational commitment has a significant effect on job satisfaction. Organizational commitment does not have a significant effect on turnover intention. Job satisfaction does not have a significant effect on turnover intention. Organizational commitment has a significant negative effect on turnover intention through job satisfaction as a mediating variable.